RoboMan: An Adult-Sized Humanoid Robot with Enhanced Performance, Inherent Stability, and Two-Stage Balance Control to Facilitate Research on Humanoids - Vahid Mohammadi; Mojtaba Hosseini; Farhad Jafari; Ahad Behboodi (Robotics, 2024)
Creating an adult-sized humanoid robot with stable walking capabilities is a major challenge in robotics. While many renowned research groups focus on robots for perilous work environments and precision tasks, our approach simplifies balance control, making it accessible to robotics research groups and educational institutes. This facilitates the development of complex functionalities such as vision and object manipulation for adult-sized humanoids. This research article introduces RoboMan II, an advanced version of RoboMan I, which won the most prestigious award in all humanoid robot leagues at RoboCup 2016 due to its exceptional performance in walking and playing soccer. RoboMan II features significant improvements in performance, inherent stability, recovery after falls, and balance control. To facilitate its development, RoboMan II is lighter and incorporates a modified foot and parallel structure for its leg to boost its inherent stability, along with a two-stage balance control system for Immediate Response and Gradual Adaptation, enhancing its adaptability in various environments. Our simulation results demonstrate that RoboMan II’s walking stability on flat surfaces improved significantly in the face of minor perturbations, with the number of steps within the stable region increasing from 24%, with only the immediate controller to 58% when both controllers were used. Similar improvements were observed on inclined surfaces. Additionally, the 3D CAD files for all of the robot parts are released as open source in conjunction with this paper to facilitate reproduction and further innovation. The forthcoming RoboMan III will incorporate custom servo motors for increased speed, torque, and enhanced fall recovery, preventing disengagement of the gear box after a fall. It promises to be an invaluable asset for research and practical applications in humanoid robotics.